Spin-Filtering Transport in Double Parallel Quantum Wires on a Graphene Sheet*Supported by the National Natural Science Foundation of China under Grant Nos. 11174214, 11204192, the NSAF Joint Fund Jointly set up by the National Natural Science Foundation of China and the Chinese Academy of Engineering Physics under Grant Nos. U1230201 and U1430117. (1st March 2015) - Yang, Fu-Bin; Cheng, Yan; Liu, Fu-Ti; Chen, Xiang-Rong; Cai, Ling-Cang
Abstract We theoretically investigate the spin filtering transport of double parallel quantum wires (QWs) side-coupled to a graphene sheet and sandwiched between two ferromagnetic (FM) leads. The dependences of the wire-graphene coupling strength, wire-wire coupling strength, as well as the spin polarization of the ferromagnetic leads are studied. It is found that the wire-graphene coupling strength tends to reduce the current and the wire-wire coupling strength can first reinforce and then decrease the current. The spin polarization strength has an enhanced (identical) effect on the current under the parallel (anti-parallel) alignment of the FM leads, which gives rise to an obvious spin-filter and tunnel magnetoresistance (TMR) effect. Our results suggest that such a theoretical model can stimulate some experimental investigations about the spin-filter devices.